Relationship between Personality Traits, Religiousity and Happiness with General Health among Nursing Students - Z Maleki; S Ashkan; J Ashoori; N Yosefi (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: General health is not determined just by disease and its treatment, but it depends on other psychological and social conditions. Among these conditions, personality trait, religiosity and happiness could be considered as the most important. This study aimed to determine the relationship between personality trait, religiosity and happiness with general health among nursing students.   Material & Methods: It was a descriptive, correlational study. The research population included all nursing students of Islamic Azad University of Varamin-Pishva Branch in 2012-13 academic years. Totally 140 nursing students (96 females and 44 males) were selected by stratified random sampling. All of them completed the questionnaires including Costa and McCrae personality trait, Allport and Ross religiosity orientation, Argyle and Luo happiness and Goldberg and Hillier general health. Data was analyzed using Pearson correlation and stepwise regression using of SPSS-PC (v.19).   Results: neuroticism (r=-0/42) had a negative significant relationship with general health and extroversion (r=0/27), agreeableness (r=0/31), conscientiousness (r=0/22), internal religiosity orientations (r=0/36) and happiness (r=0/27) showed a positive significant relationship with general health (P<0/05). In a predictor model, only neuroticism, internal religiosity orientations, happiness and extroversion predicted 37 percent of general health. The share of neuroticism was higher compared to other variables.   Conclusion: According to the findings, neuroticism, internal religiosity orientations, happiness and extroversion were the most important predictors of general health. Therefore, it is suggested that planners, therapists and psychosocial counselors consider the symptoms of these variables and design appropriate programs to improve the general health of nursing students.